Optimizing On-The-Job Training in Obstetrics and Gynecology Fellowship: A Learning Theory-Based Framework for Competency Development - Nawaz, Qudsia; Ghaffar, Sadia Abdul; Shafiq, Sadia; Tufail, Shazia; Rehman, Mounazza; Khan, Junaid Sarfaraz; Nawaz, Sadia (Biological and Clinical Sciences Research Journal, 2025)
In Pakistan, the current on-the-job training (OJT) model for Obstetrics and Gynecology (Ob-Gyn) fellowship programs primarily follows an apprenticeship-based framework. While this model offers experiential benefits, it presents notable challenges in standardized competency development, structured mentorship, and consistent feedback, thereby affecting training quality and skill acquisition. Objective: To evaluate the effectiveness of the existing OJT model in Ob-Gyn fellowship training in Pakistan using established learning theories and to propose a structured framework for optimizing training outcomes. Methods: A qualitative literature review was conducted to assess the existing OJT model through the lens of competency-based medical education, experiential learning theory (Kolb), and social learning theory (Bandura). Sources included peer-reviewed journals, academic reports, and international training guidelines. The analysis focused on identifying strengths and gaps within the current system. A framework for training enhancement was subsequently developed, incorporating principles of structured mentorship, simulation-based education, standardized rotations, and objective assessment tools. Results: The review revealed that while the current OJT model aligns well with experiential and social learning theories, it suffers from critical gaps. These include non-uniform case exposure, limited use of simulation technologies, inconsistent formative feedback, and lack of standardized evaluation metrics. The proposed framework includes structured mentorship programs, integration of simulation-based modules, objective assessment criteria (e.g., DOPS, OSATS), and technology-assisted learning platforms, all aimed at enhancing trainee competence and aligning with international best practices. Conclusion: The OJT model in Ob-Gyn fellowship training in Pakistan can be significantly strengthened by adopting a hybrid approach. Integrating simulation-based education, structured feedback systems, standardized competency assessments, and enhanced mentorship will bridge existing gaps and elevate the training program to meet global standards.